Workflow for the Implementation of Precision Genomics in Healthcare - Mehandziska, Sanja; Stajkovska, Aleksandra; Stavrevska, Margarita; Jakovleva, Kristina; Janevska, Marija; Rosalia, Rodney; Kungulovski, Ivan; Mitrev, Zan; Kungulovski, Goran (Frontiers in Genetics, 2020)
To enable the implementation of precise genomics in a local healthcare system, we devised a pipeline for filtering and reporting of relevant genetic information to healthy individuals based on exome or genome data. In our analytical pipeline, the first tier of filtering is variant-centric and it is based on the selection of annotated pathogenic, protective, risk factor and drug response variants, and their one-by-one detailed evaluation. This is followed by a second-tier gene-centric deconstruction and filtering of virtual gene lists associated with diseases, and VUS-centric filtering according to ACMG pathogenicity criteria and pre-defined deleteriousness criteria. By applying this filtering protocol, we were able to provide valuable insights regarding the carrier status, pharmacogenetic profile, actionable cardiovascular and cancer predispositions, and potentially pathogenic variants of unknown significance to our patients. Our experience demonstrates that genomic profiling can be implemented into routine healthcare and provide information of medical significance.